Kinerja Institusi DP3APPKB dalam Pelaksanaan Program Pelayanan Pusat Pembelajaran Keluarga Surabaya - Anggun Tri Mawardani; Indira Arundinasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Research related to the performance of the Department of Women's Empowerment and Child Protection as well as Population Control and Family Planning (DP3APPKB) in implementing the PUSPAGA Surabaya service program is an important thing to carry out considering that there are still high cases of child violence in Surabaya and the government of Surabaya must maintain its achievements as a Child Friendly City at a high level six times in a row. This research was conducted at DP3APPKB Surabaya. The purpose of this research is to determine, describe and analyze the level of organizational performance at the DP3APPKB Service in implementing the PUSPAGA Surabaya service program. The research method used is qualitative with a case study approach. The theory used is the theory of organizational performance according to Soesilo in Tangkilisan (2005) which includes organizational structure, management policies, human resources, management information systems and facilities and infrastructure. This research is related to the performance of the organization at DP3APPKB in implementing the PUSPAGA Surabaya service program. The results of this research indicate that the performance of DP3APPKB Surabaya in implementing the PUSPAGA Surabaya service program has been carried out quite well, because there are still several obstacles such as, PUSPAGA public halls not carrying out tasks or job desks in accordance with the division of the organizational structure, unequal distribution of human resources in providing services PUSPAGA Surabaya, especially for public halls that do not receive volunteer assistance from DP3APPKB Surabaya. Furthermore, most Surabaya residents do not know the use of the SIAP PPAK application which is used as a tool to measure the success of online consultation services and database management in implementing the PUSPAGA Surabaya service program. The facilities and infrastructure of PUSPAGA Surabaya are quite good and have followed the guidelines from the Ministry of PPA, but this does not apply to PUSPAGA public halls.